“Creación de aplicativo móvil de lectura de inventario a través de realidad aumentada para laboratorio de electromecánica de la Universidad Técnica de Cotopaxi Extensión - La Maná.” - Cercado Basurto, David Alexander (2022)
The Technical University of Cotopaxi, La Maná extension, has humanistic and technical careers in the latter, we can find the career of Electromechanics which has laboratories with a variety of equipment and instruments for the use of professors and students to perform academic activities and practices. There is a lack of knowledge about the use and manipulation of the tools, and their characteristics, which is the reason the equipment and tools are not systematized. As a consequence of the above, we propose to create a mobile application for inventory reading through augmented reality for the laboratory. The augmented reality markers were used for the effect of the equipment modeled in 3D, taking the visualization of the same in the form of dynamic, interactive, and entertaining learning that allows the reading of the markers using the Vuforia camera and 3D modeling and the Unity engine, for the development process of the mobile application was applied the Mobile-D methodology. According to the user experience, the application is functional and useful and has elements of how to initiate, which is the access to augmented reality, the gallery presents all the objects modeled in 3D, resources are the triggers, and the inventory is generated by the application itself. To conclude, the application was developed in Unity and Vuforia for Android operating systems version 8 onwards and therefore for the respective installation and manipulation of professors and students were trained, who will perform the support and scalability.